Exchange Rate against Dollar- A Challenge for Indian Economic Development - Sabitha, G. (International Journal of Psychosocial Rehabilitation, 2020)
This study made an attempt know the role of rupee vs. Dollar impact on Indian economy in the period 2000-01 to 2017-18. The secondary data has been considered and the ADF test has been applied to remove the seasonality effect from the time series data. The bivariate correlation has been applied and found that all the selected economic factors are having a stronger relationship with the currency of rupee with the dollar. The linear regression result stated that the inflation and the exports are positively influenced by the currency. The VAR model predicted that in near future all the selected economic variables are expected to go down if the currency gets depreciated against the dollar. Correlation of rupee vs dollar has been identified to be varying with each of IIP, BOP and Inflation as negatively correlated, moderately correlated and positively correlated respectively. All the above mentioned statistical tests have been used in this study to determine the relationship of the independent variable exchange rate with all other dependent variables considered in the study.